Reduction of corn particle size in lactation diets improves sow and litter performance - Wondra, K.J.; Kennedy, G.A.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred primiparous sows were used to determine the effects of corn particle size in lactation diets on sow and litter performance. Sows were fed com-soybean mealbased diet with the com ground to 1,200, 900, 600, or 400 JLm. Particle size of corn had no influence on sow weight or backfat loss, or piglet survivability. However, feed intake and digestibilities of DM, N, and GE were increased (6, 5, 7, and 7%, respectively) as particle size was reduced from 1,200 to 400 JLm. The combination of increased feed intake and improved digestibilities resulted in increased intake of digestible nutrients. DE intake was increased 14% (13.72 to 15.60 Mcal/d) as com particle size was reduced from 1,200 to 400 JLm. Intakes of digestible DM and N were also increased (11 and 14%, respectively). The increased intake of digestible nutrients resulted in a 11% increase in litter weight gain. Reducing particle size increased severity of keratinization and lesions in the esophageal region of the stomach although all treatment averages were low to moderate, and the change was not associated with reduced sow performance. In conclusion, our data indicate that nutrient intake of sows and litter weight gains can be increased by grinding corn for lactation diets to particle sizes of 600 to 400 JLm.
Keywords: Swine; Process; Particle Size; Sow; Lactation; Stomach ulcers